INDUSTRY AND ACADEMIA COLLABORATION IN ADDRESSING THE THEORY AND PRACTICE GAP BUSINESS AND MANAGEMENT EDUCATION (A SYSTEMATIC LITERATURE REVIEW) - Sumiati; Sa’diyah, Yuni Aminatus; Sugihartono, Agus; Kusumawardani, Luluk Nur Indah; Narmaditya, Bagus Shandy; Wardana, Ludi Wishnu (Nusantara Economics and Entrepreneurships Journals, 2024)
This study aims to explore the role of collaboration between industry and academia in addressing various challenges faced in business and management education. The research employs case studies and qualitative analysis, with data collected through in-depth interviews with faculty members, students, and industry practitioners at several universities in Indonesia. The findings indicate that effective collaboration between industry and academia can bridge the gap between theory and practice, enrich the curriculum, and enhance graduates' readiness for the job market. Additionally, this collaboration helps in providing better resources, such as technology and educational facilities. The study concludes that strategic and sustainable collaboration between industry and academia is crucial for improving the quality of business and management education and producing more competent and job-ready graduates. Strategic recommendations include enhancing communication and cooperation between academia and industry, developing more comprehensive internship programs, and aligning the curriculum with industry needs.